Constrained Cyclic β, γ‐Diamino Acids from Glutamic Acid: Synthesis of Both Diastereomers and Unexpected Kinetic Resolution. Issue 3 (18th January 2018) - Wan, Yang; Auberger, Nicolas; Thétiot‐Laurent, Sophie; Bouillère, Francelin; Zulauf, Anaïs; He, Jiefang; Courtiol‐Legourd, Stéphanie; Guillot, Régis; Kouklovsky, Cyrille; Cote des Combes, Sylvain; Pacaud, Christophe; Devillers, Ingrid; et al.
Abstract : We describe here an efficient synthesis of both diastereomers of cyclic β, γ‐diamino acids starting froml ‐glutamic acid, based on the Blaise reaction. We show that by changing the protecting group, we can access either the five‐membered‐ring lactam, which can be used as a β‐amino acid, or the six‐membered‐ring lactam, as a γ‐amino acid. We also discovered an interesting kinetic resolution during the synthesis that allowed easier separation of diastereomers. The products can be easily used in peptide synthesis, and a tetramer with alternating trans cyclic γ‐amino acid and AIB (2‐aminoisobutyric acid) residues was synthesized. Abstract : Constrained cyclic β, γ‐diamino acids were synthesized starting froml ‐glutamic acid. The key steps were a Blaise reaction and a reduction that gave access to both diastereomers. Changing the protecting group can lead to either the five‐membered‐ring lactam, which can be used as a β‐amino acid, or to the six‐membered‐ring lactam, as a γ‐amino acid.